SALARY, INCENTIVES, AND EMPLOYEE PRODUCTIVITY: (Case Study of USPPS BMT Al-Hijrah KAN Jabung) - Alamsyah, Dodik; Setyawati, Dyah; Nurwijayanto, Putra Ramadhani; Santi, Fitriana; Aman, Yosanda Zata (Airlangga International Journal of Islamic Economics and Finance, 2024)
The study aims to analyze the impact of salary and incentives on employee productivity at USPPS BMT Al-Hijrah KAN Jabung Syariah from both simultaneous and partial perspectives. The research employs multiple regression analysis, with a sample population consisting of all 40 employees, who were also the subjects of the study. The analysis results indicate that salary has a positive and significant effect on employee productivity. Additionally, incentives also contribute positively and significantly to productivity. The findings of this research are expected to provide valuable insights for continuous improvement at USPPS BMT Al-Hijrah KAN Jabung Syariah